Student’s perception of school bullying and its impact on academic performance: A longitudinal look - Zalba, Julieta; Durán, Lucas G; Carletti, Diego R; Zavala Gottau, Patxi; Serralunga, María G; Jouglard, Ezequiel F; Esandi, María E (Archivos argentinos de pediatría, 2018)
Bullying among peers has immediate and long-term consequences, as it affects children's health-related quality of life. The aim was to examine the association between the frequency, type and dynamics of children's involvement in bullying situations and their academic performance over the school year. Longitudinal study conducted in 2015 in 9 to 12 year-olds in schools of Bahía Blanca, Argentina. Outcome measures: children's involvement in bullying situations, frequency of participation in bullying and academic performance. Bullying categories were obtained through the Preconceptions of Bullying and Intimidation Among Peers (PRECONCIMEI) questionnaire and academic performance as reflected by each child's school grades. The survey included 375 children, of which 22.1% (83/375) were repeatedly involved and 30.12% (113/375) were occasionally involved in bullying situations (20.27% [76/375] reported having participated by the year end but not at the beginning, and 9.85% [37/375] showed the opposite behavior). No statistically significant differences were found, regardless of the course subject analyzed. Grades were found to have improved by school year-end, in all groups assessed. No association was found between bullying and academic performance.